Quantifying Climate Risk and Building Resilience in the UK - Dessai, Suraje; Lonsdale, Kate; Lowe, Jason; Harcourt, Rachel (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book draws together key research from the UK Climate Resilience programme. It focuses on topics central to the programme's research agenda, including improved characterisation and quantification of climate risks, enhanced understanding of the management of climate risks, and the development and delivery of climate services. Key chapters address the challenges inherent to undertaking resilience research, including how to make the term 'climate resilience' usable and useful, co-producing research between academics, policy makers and practitioners, and engaging and communicating outside of academia. This book is unique in providing a concise and accessible overview of the programme's key lessons, placing the findings into a wider context and it will inform future research, policy and practice agendas. Suraje Dessai is Professor of Climate Change Adaptation in the School of Earth and Environment at the University of Leeds. Kate Lonsdale is a Director at Climate Sense, a group that supports organisations to navigate the complex internal and external challenges of decision making for adaptation. Jason Lowe is Chair in Interdisciplinary Climate Research at the Priestley Centre at the University of Leeds and Head of Climate Services/Principal Fellow at the Met Office. Rachel Harcourt is a research fellow in climate resilience in the Priestley Centre at the University of Leeds.